HUBUNGAN ASUPAN SERAT, ADVANCED GLYCATION END PRODUCTS (AGEs) DAN AKTIVITAS FISIK DENGAN KADAR HBA1C PASIEN RETINOPATI DIABETIK DI RAWAT JALAN PUSAT MATA NASIONAL RUMAH SAKIT MATA CICENDO BANDUNG - Rahmawati, Mutia Fadhillah (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
ABSTRACT Diabetes mellitus is a chronic metabolic disorder disease characterized by blood sugar levels exceeding normal limits. Based on medical record data, it shows that diabetic retinopathy is the highest complication of diabetes mellitus in the National Eye Center Cicendo Eye Hospital Bandung. The purpose of this study was to determine the relationship between fiber intake, advanced glycation end products (AGEs) and physical activity with HbA1c levels in diabetic retinopathy patients at the National Eye Center Outpatient Center Cicendo Eye Hospital Bandung. The study was conducted in December 2021 using a cross sectional research design with accidental sampling technique involving 40 samples, namely patients with a diagnosis of diabetic retinopathy based on doctors. Data collection using a questionnaire includes primary data and secondary data. Data on HbA1c levels were obtained from secondary data in the electronic medical record (EMR), data on fiber intake and AGEs were obtained by interview using the SQFFQ form, and physical activity data obtained by interview using the IPAQ form. Data analysis was carried out univariate and bivariate using the Chi Square test on AGEs and physical activity, as well as Spearman's test on fiber intake. The results showed that 40 samples had less fiber intake (100%), 30 samples had more AGEs (75%) intake and 16 samples had moderate (40%) physical activity. Based on the Chi Square test, the p-value of AGEs intake was 0.032 where p <0.05 and physical activity p-value was 0.028 (p <0.05). In fiber intake, the p-value is 0.663 (> 0.05) and the correlation coefficient is 0.071. Conclusion: there is a relationship between intake of AGEs, physical activity with HbA1c levels in diabetic retinopathy patients and there is no relationship between fiber intake and HbA1c levels in diabetic retinopathy patients. Keywords: Fiber Intake, Advanced Glycation End Products (AGEs), Physical Activity, HbA1c Levels, Diabetic Retinopathy